Analysis of Consumption Behavior of Linggajaya Village Community - Rani Wahyuni; Harnavela Sofyan (STAI MA'ARIF MAGETAN, INDONESIA, 2026)
Consumptive behavior is the tendency of individuals to purchase goods or services that are not always based on actual needs, but are influenced by desires, trends, and social environmental factors. This study aims to determine the level of consumptive behavior among the people of Linggajaya Village, the factors that influence it, and the efforts made by the community to reduce consumptive behavior in daily life.This research uses a descriptive quantitative method with data collection techniques through structured questionnaires distributed to the community of Linggajaya Village, Tasikmalaya City. The sample was determined using purposive sampling, selecting respondents who were considered representative of the community. The collected data were then analyzed descriptively to describe patterns of consumptive behavior.The results show that the level of consumptive behavior among the people of Linggajaya Village is relatively high, particularly in the form of impulsive buying, purchases driven by promotions or discounts, and the tendency to follow trends on social media. Factors influencing consumptive behavior include individual, psychological, social, technological, and financial literacy factors. Therefore, it is necessary to improve awareness and education regarding financial management so that people can make wiser consumption decisions.